Precise Fecal Microbiome of the Herbivorous Tibetan Antelope Inhabiting High-Altitude Alpine Plateau - Bai, Xiangning; Lu, Shan; Yang, Jing; Jin, Dong; Pu, Ji; Díaz Moyá, Sara; Xiong, Yanwen; Rossello-Mora, Ramon; Xu, Jianguo (Frontiers in Microbiology, 2018)
The metataxonomic approach combining 16S rRNA gene amplicon sequencing using the PacBio technology with the application of the operational phylogenetic unit (OPU) approach, has been used to analyze the fecal microbial composition of the high-altitude and herbivorous Tibetan antelopes. The fecal samples of the antelope were collected in Hoh Xil National Nature Reserve, at an altitude over 4500 m, the largest depopulated zone in Qinghai-Tibetan Plateau, China, where non-native animals or humans may experience life-threatening acute mountain sickness. In total, 104 antelope fecal samples were enrolled in this study, and were clustered into 61,258 operational taxonomic units (OTUs) at an identity of 98.7% and affiliated with 757 OPUs, including 144 known species, 256 potentially new species, 103 potentially higher taxa within known lineages. In addition, 254 comprised sequences not affiliating with any known family, and the closest relatives were unclassified lineages of existing orders or classes. A total of 42 out of 757 OPUs conformed to the core fecal microbiome, of which four major lineages, namely, un-cultured Ruminococcaceae, Lachnospiraceae, Akkermansia and Christensenellaceae were associated with human health or longevity. The current study reveals that the fecal core microbiome of antelope is mainly composited of uncultured bacteria. The most abundant core taxa, namely, uncultured Ruminococcaceae, uncultured Akkermansia, uncultured Bacteroides, uncultured Christensenellaceae, uncultured Mollicutes, and uncultured Lachnospiraceae, may represent new bacterial candidates at high taxa levels, and several may have beneficial roles in health promotion or anti-intestinal dysbiosis. These organisms should be further isolated and evaluated for potential effect on human health and longevity.